François Gros : Une personnalité de premier plan, un homme secret - Robert, Benoît (Comptes Rendus Biologies)
I joined François Gros’ laboratory in 1975, to study mechanisms of gene expression in eukaryotes. Despite the lack of powerful tools, that would be brought later by genetic engineering, I obtained publishable results and was allowed to defend a third cycle thesis. Thereafter, I joined Margaret Buckingham’s group, which was empowering within François’ laboratory. I maintained regular meetings with François, a leading figure but a secretive man, who did not readily open up. It was my privilege, over the more than 45 years I have been around him, to have glimpses over what had been really significant to him. This has been a rich and very precious experience.